Kedudukan Penerima Fidusia Dalam Proses Penyelesaian Wanprestasi Atas Objek Jaminan Yang Dikuasai Oleh Negara - Juandre, Soja; Lestari, Rika; Firmanda, Hengki (Peneliti.net, 2024)
The confiscation of a fiduciary object by the state due to an unlawful act is considered negligence by the fiduciary and the fiduciary must be held responsible. As happened in the Civil Lawsuit Decision Number 142/Pdt.G/2021/PN Pbr, where the party receiving the fiduciary tried to defend his rights because the object which was the object of the fiduciary guarantee was confiscated by the state due to the negligence of the fiduciary giver. The preferential right of the fiduciary recipient here becomes questionable when the object that is the object of the fiduciary guarantee is no longer in the hands of the debtor because the object is confiscated by the state. However, the confiscation of the object that is the object of the fiduciary guarantee here does not make the fiduciary guarantee invalid/destroyed, the fiduciary giver still has to resolve the default against the party receiving the fiduciary. The author aims to analyze how the position of the fiduciary recipient, namely as a preferred creditor, and the material rights owned by the fiduciary recipient are linked when the object that is the object of the fiduciary guarantee is confiscated by the state. Apart from that, the author also examines the process of resolving defaults when objects that are the object of collateral are confiscated by the state. The conclusions obtained from the results of this research are first, the creditor, in this case PT MCF, has material rights so it is classified as a preferred creditor. The priority right in question is the right of the fiduciary recipient to collect the receivables for the proceeds from the execution of the object that is the object of the fiduciary guarantee. The preferred position of creditors is obtained, among other things, if they have material rights. Second, negligence regarding collateral objects is the debtor's responsibility. The creditor, namely PT MCF, who felt aggrieved as a result of the debtor's actions, submitted a request to the presiding judge at the trial examining the criminal case. Then, of course, the person being sued is the debtor as the provider of the fiduciary guarantee. The PT finally filed a lawsuit at the Bangkinang District Court which ended with a deed of peace stating that the collateral object would be returned to the creditor and auctioned off as repayment of the debtor's debt.